PENGEMBANGAN LAYANAN AKADEMIK DAN MEDIA PEMBELAJARAN BERBASIS INFORMATION AND COMMUNICATION TECHNOLOGY DI STAIN PAMEKASAN - Erie Hariyanto (Research Institute and Community Engagement of IAIN MADURA, 2015)
Rapidly developed information technology makes college adjust the need of academic service to the information technology. Academic service and learning media ICT based that used in teaching learning process in STAIN Pamekasan from time to time experiencing rapidly develops both quality and quantity. Nowadays, college introduces online academic service (AIDA) besides infrastructure. STAIN Pamekasan has completed the need such as multimedia room, microteaching room, and computer laboratory. Most of them use projector LCD, Google apps, learning by module, and instructor private blog. If the use of them is supported by good desirability and integrity, it can be used to make interesting, interactive, and qualitative lecturing. Finally, it is able to make professional and excellent alumnus and aware of the development of technology.